2018
DOI: 10.1093/mnras/sty3482
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing circumgalactic gas around massive ellipticals atz∼ 0.4 – II. Physical properties and elemental abundances

Abstract: We present a systematic investigation of the circumgalactic medium (CGM) within projected distances d < 160 kpc of luminous red galaxies (LRGs). The sample comprises 16 intermediate-redshift (z = 0.21−0.55) LRGs of stellar mass M star > 10 11 M . Combining far-ultraviolet Cosmic Origin Spectrograph spectra from the Hubble Space Telescope and optical echelle spectra from the ground enables a detailed ionization analysis based on resolved component structures of a suite of absorption transitions, including the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
135
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 105 publications
20
135
1
Order By: Relevance
“…The measured O VI column densities (N OVI > 10 13.9 cm −2 ) are similar to the typical O VI columns found surrounding low-redshift galaxies Johnson et al 2015Johnson et al , 2017Zahedy et al 2018) and also the typical column den- Figure 6. The velocities and impact parameters of metal-enriched absorbers within 100 pkpc of a galaxy in the KBSS sample.…”
Section: Comparison To Theory and Other Observationssupporting
confidence: 78%
See 2 more Smart Citations
“…The measured O VI column densities (N OVI > 10 13.9 cm −2 ) are similar to the typical O VI columns found surrounding low-redshift galaxies Johnson et al 2015Johnson et al , 2017Zahedy et al 2018) and also the typical column den- Figure 6. The velocities and impact parameters of metal-enriched absorbers within 100 pkpc of a galaxy in the KBSS sample.…”
Section: Comparison To Theory and Other Observationssupporting
confidence: 78%
“…Given the generally high inferred temperatures of the O VI absorbers, we do not compare directly to the models proposed by Stern et al (2018) where the gas is photoionized; however, we note that the absorbers with lower inferred temperatures may be better described by such a model (see e.g. Zahedy et al 2018). Alternatively, absorbers with low inferred temperatures could be over-ionized gas that has rapidly cooled.…”
Section: The Doppler Widths Of O VI Absorbersmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, Johnson et al (2017) showed that star-forming field dwarfs of <0.1 L * without massive neighbours account for ≈20 per cent of O VI absorption systems with rest equivalent widths stronger than ≈0.1Å, and that this phase of their CGM likely dominates the baryon budget of these low-mass systems. More recently, Chen et al (2018) and Zahedy et al (2019) showed that O VI absorption systems with logN(O VI) > 13.5 are common in the CGM of luminous, quiescent galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases the material was assumed to be irradiated with a redshift zero Haardt & Madau (2012) (HM2012) EUVB whose specific intensity was normalized to 8.23 × 10 −24 erg cm −2 s −1 Hz −1 sr −1 at the Lyman limit following the radio-quiet AGN spectral index (α = 0.157). Note that our simulations assume chemical homogeneity, while observations indicate that the composition of the CGM is likely to be significantly inhomogeneous (Zahedy et al 2019). However, the impact of this additional factor is left for future investigation.…”
Section: Model Parametersmentioning
confidence: 93%